Jayanta Bhaṭṭakṛta Pramāṇamīmāṃsā paryālocanam - Bhaṭṭācārya, Ayana (Saṃskṛta Buka Ḍipo, 2012)
Critical study of the commentary on Gautama's Nyāyasūtra, aphoristic work of the Nyaya school in Hindu philosophy